2020
DOI: 10.1021/acs.jpca.9b09985
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Investigation of Dimerization in the Schlenk Equilibrium of Thiophene Grignard Reagents

Abstract: The Schlenk equilibrium of Grignard reagents describes the intricate relationships between monomers, aggregates, and exchange products. The core step of the Schlenk equilibrium, formally 2RMgX ⇌ R 2 Mg + MgX 2 , has been subject to computational studies of simple methyl Grignards and NMR determination of thermodynamics. These studies neglect the effect the R group may have on the accessibility of intermediates in the Schlenk equilibrium. In this study, computational reaction discovery tools were employed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Recent computational studies of aryl Grignard reagents have revealed stable dimeric aggregates that sequester reactive monomer and push the equilibrium away from the chain-bound structures required in our proposed mechanism . We identified two such dimeric aggregates for 1-MgBr (Figure S20).…”
Section: Results and Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Recent computational studies of aryl Grignard reagents have revealed stable dimeric aggregates that sequester reactive monomer and push the equilibrium away from the chain-bound structures required in our proposed mechanism . We identified two such dimeric aggregates for 1-MgBr (Figure S20).…”
Section: Results and Discussionmentioning
confidence: 79%
“…To understand why this reaction fails, we performed calculations for monomer coordination to the thiophene dimer radical anion, 12 (Figure a; the hexyl chain is truncated to CH 3 ), which would be produced by oxidative dimerization of the corresponding Grignard monomer. Recent computational work by Zimmerman on the aggregation of thiophene Grignard reagents suggests that thiophenes such as 2-MgBr form stable solvate dimers . Such dimers would decrease reactivity by pushing the equilibrium away from the necessary monomer-coordinated radical anions.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations